2021
DOI: 10.1101/2021.09.11.459896
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cold shock induces a terminal investment reproductive response in C. elegans

Abstract: Challenges from environmental stressors have a profound impact on many life-history traits of an organism, including reproductive strategy. Examples across multiple taxa have demonstrated that maternal reproductive investment resulting from stress can improve offspring survival; a form of matricidal provisioning when death appears imminent is known as terminal investment. Here we report a reproductive response in the nematode Caenorhabditis elegans upon exposure to acute cold shock at 2C, whereby vitellogenic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…SOAT converts accessible cholesterol into ester forms for storage in lipid droplets (Luo et al 2020; Sevanian & Peterson 1986). While the biochemical function of OAC-31 remains further characterized, a recent study showed that cold shock can promote lipid movement from the intestine to the germline (Gulyas & Powell 2021). Interestingly, natural aging of C. elegans is accompanied with autophagy-mediated conversion of intestinal biomass into yolk, contributing to late-life aging pathologies and mortality (Ezcurra et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SOAT converts accessible cholesterol into ester forms for storage in lipid droplets (Luo et al 2020; Sevanian & Peterson 1986). While the biochemical function of OAC-31 remains further characterized, a recent study showed that cold shock can promote lipid movement from the intestine to the germline (Gulyas & Powell 2021). Interestingly, natural aging of C. elegans is accompanied with autophagy-mediated conversion of intestinal biomass into yolk, contributing to late-life aging pathologies and mortality (Ezcurra et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that genetic programs underlying stress-induced phenoptosis may have evolved because of antagonistic pleiotropic effects and/or “kin selection” at the population level so that the phenoptosis of adult and weak individuals after severe cold-thermal stress would benefit less stressed and reproductively more privileged ones to facilitate the spreading of genes by fit individuals under resource-limiting and high-stress conditions (Jiang et al 2018; Hamilton 1963; Smith 1964). While evolutionary mechanisms and significance of phenoptosis still remain debatable in the field (Galimov et al 2019; Kirkwood & Melov 2011; Longo et al 2005; Sapolsky 2004; Skulachev 2019), many empirical studies suggest that organisms with clonal population structures such as C. elegans may indeed chronically age or die under stresses by mechanisms (terminal investment, antagonistic pleiotropy, consumer sacrifice or disposable soma) that can benefit its progeny or reproductive success of the organism itself (Ezcurra et al 2018; Galimov & Gems 2020; Gulyas & Powell 2021; Wu et al 2022).…”
Section: Introductionmentioning
confidence: 99%